Islam, Fatwa dan Negara: Pluralisme Hukum Perceraian di Aceh, Indonesia - Muhazir, Muhazir (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
This article examines the Legal pluralism of divorce in Aceh, even though the government has regulated divorce laws that apply nationally. However, the Ulama Consultative Assembly (MPU) of Aceh Has issued a fatwa whose legal substance was different from the divorce regulations made by the government, coupled with the legal conditions for divorce in Acehnese people who are fanatical to the school (mazhab) of Shafi'i which is theoretically different from the divorce law in Indonesia. This type of research is doctrinal with a legal pluralism approach. This article aims to analyze the dynamics of divorce law in Acehnese society. The results show that there are three kinds of law that normatively and sociologically apply in Aceh, namely fikih munakat, fatwa and state law, and each has its own legal concept regarding divorce.